Hack Days as a Method to Increase Interdisciplinary Knowledge and Collaboration Skills of College Students in STEM Fields - Tandon, James; Pakpour, Nazzy; Gumina, Mario (Journal of Interdisciplinary Studies in Education, 2021)
Providing college students with learning experiences that account for the interdisciplinary nature of most STEM professions has proven challenging. STEM educational practices typically follow a more scripted process designed to build important foundational skills. In contrast, most STEM professions are interdisciplinary and collaborative in nature. Thus, a gap in experience is created that needs to be addressed if we desire our students to be successful. One potential solution is to hold extra-curricular events, such as a hack day, to provide students with collaborative interdisciplinary learning experiences. We held two such hack day events and found that these events were a highly effective at increasing both the interest and interdisciplinary knowledge of undergraduates.